Chronic obstructive pulmonary disease prognostic score: A new index - Horita, Nobuyuki; Koblizek, Vladimir; Plutinsky, Marek; Novotna, Barbora; Hejduk, Karel; Kaneko, Takeshi (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2016)
BACKGROUND: The evaluation of chronic obstructive pulmonary disease (COPD) has been shifting from spirometry to focus on the patients' overall health. Despite the existence of many COPD prognostic scales, there remains a large gap for improvement, in particular a scale that incorporates the current focus on overall health. METHODS: We proposed a new prognostic scale (the COPD Prognostic Score) through discussion among the authors based on published studies. Validation was retrospective, using data from the National Emphysema Treatment Trial. RESULTS: The scores ranged from 0-16, where 16 indicated the poorest prognosis. We assigned 4 points each for forced expiratory volume in one second (%predicted), the modified Medical Research Council dyspnea scale, and age; 2 points for the hemoglobin level; and one point each for decreased activity and respiratory emergency admission in the last two years. The validation cohort included 607 patients and consisted of 388 men (73.9%) and 219 women (36.1%), mean age 67 ± 6 years and an average forced expiratory volume in one second (% predicted) of 27 ± 7%. A one-point increase in the score was associated with increased all-cause death, with a hazard ratio of 1.28 (95%CI: 1.21-1.36. P < 0.001). The areas under the receiver operating characteristic curves for two-year and five-year all-cause death for the new scale were 0.72 and 0.66, respectively. These values were higher than those given by the body mass index, airflow obstruction, dyspnea, and exercise capacity (BODE) index and age, dyspnea, airway obstruction (ADO) index. CONCLUSION: The preliminary validation for a new COPD prognostic scale: the COPD Prognostic Score was developed with promising results thus far. Above mentioned 16-point score accurately predicted 2-year and 5-year all-cause mortality among subjects who suffered from severe and very severe COPD.
Keywords: Spirometry; spirometrie; Aged; dyspnea; Hemoglobins; Forced Expiratory Volume; stupeň závažnosti nemoci; Retrospective Studies; lidé středního věku; senioři; prognóza; Severity of Illness Index; lidé; Middle Aged; průzkumy a dotazníky; Prognosis; Kaplan-Meier Estimate; hemoglobiny; Female; spirometry; Dyspnea; Surveys and Questionnaires; Male; ženské pohlaví; Humans; mužské pohlaví; Kaplanův-Meierův odhad; Walking; COPD; hemoglobin; age; Pulmonary Disease, Chronic Obstructive; dyspnoe; chronická obstrukční plicní nemoc; prognosis; chůze; usilovný výdechový objem; retrospektivní studie